Computers and the family life: a family development perspective. - Watt, David; White James M (Journal of Comparative Family Studies)
The purpose of this paper is to review issues and research findings related to the effects of computer use on the family. One of the major challenges for such an undertaking is to develop a framework with which to organize relevant data and issues. The organization of this paper is based on the utilization of stages of family development. In addition to outlining seven stages of family development and associated issues pertaining to computers, propositions linking family development and ecological theory are used to explain the linkage between technological change, role change, and family development. This paper suggests a program of research for family scholars based on the theoretical orientation developed in this paper along with the current empirical findings. Reprinted by permission of the publisher.